2009
DOI: 10.1371/journal.pone.0008467
|View full text |Cite
|
Sign up to set email alerts
|

General Epidemiological Parameters of Viral Hepatitis A, B, C, and E in Six Regions of China: A Cross-Sectional Study in 2007

Abstract: BackgroundViral hepatitis is a serious health burden worldwide. To date, few reports have addressed the prevalence of hepatitis A, B, C, and E in China. Therefore, the general epidemiological parameters of viral hepatitis remain unknown.Principal FindingsIn this cross-sectional study, we performed a serological prevalence analysis of viral hepatitis A, B, C, and E in 8,762 randomly selected Chinese subjects, which represented six areas of China. The overall prevalence of anti-Hepatitis C virus antibody (anti-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
70
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 28 publications
(31 reference statements)
16
70
2
Order By: Relevance
“…Males showed a 1.2 times higher HCV infection rate than females, whereas other studies have reported equality between sexes or even female predominance in HCV infection (8,(20)(21)(22). The underlying reason of male predominance in this study is still not clear.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Males showed a 1.2 times higher HCV infection rate than females, whereas other studies have reported equality between sexes or even female predominance in HCV infection (8,(20)(21)(22). The underlying reason of male predominance in this study is still not clear.…”
Section: Discussioncontrasting
confidence: 67%
“…A seroepidemiology survey of hepatitis C infection is important for prevention and treatment of the disease (16). In 1992, the first nationwide cross-sectional seroepidemiologic survey of hepatitis C infection with a total of approximately 68,000 participants showed the prevalence of anti-HCV was 3.2% in the general population aged from 1 to 59 years (8). However, two recent studies reported a lower prevalence in the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study confirmed the results of some studies that the presence of anti-HBc among non-infected individuals generally increased with age (18,20,24,25). However in our study, the presence of anti-HBc peaked among those in the 51 -60 age group while in a previous study of a large foreign-born Chinese and Korean American sample, it peaked among those older than 60 years (8).…”
Section: Discussionsupporting
confidence: 92%
“…This rate of presence of anti-HBc was much higher than the national average (5, 6), but comparable to the results found from other studies of Asian immigrants (9,10) and studies of individuals from HBV-endemic Asian countries (20,21). Our finding indicates that Asian Americans are substantially more likely to have been exposed to HBV than the general U.S. population.…”
Section: Discussionsupporting
confidence: 86%